Clinical Efficacy of Ayurvedic Interventions in Dushta Vrana Associated with Diabetic Foot Ulcer: A Case Report - Dr. Hemanshu Maheta; Dr. Chandrakant Pawar; Dr. Shailesh Jaiswal (The Bioscan, 2026)
Diabetic foot ulcers (DFUs) are a significant source of morbidity in patients with Type 2 Diabetes Mellitus, which often lead to chronic non-healing wounds, infections and amputations. Such ulcers are also correlated in Ayurvedic literature as Dushta Vrana especially when coupled with Prameha. The current case report reports the integrative management of a 68-year-old male with a chronic diabetic foot ulcer with a history of dry gangrene and history of previous toe amputation. This ulcer was Wagner Grade 2 and it was related to peripheral neuropathy. The first management was surgical disarticulation to debride the necrotic tissue because this pre- vented local infection. This was followed by a systematic Ayurvedic treatment regimen that is guided on the concept of Vrana Shodhana and Vrana Ropana. Oral preparations such as Gandhak Rasayan, Manjisthadi Vati, Mehaabhaya Kashaya as well as Kaishor Guggulu were used together with local wound care using Jatyadi Taila and normal debridement. It was noted over the two months period with progressive wound healing, discharge reduction and consider- able wound contraction without recurrence or other complications. This case illustrates how an integrative method with necessary form of surgery alongside classical Ayurvedic treatment can be very fruitful in the treatment of diabetic foot ulcers. This kind of holistic approach helps in treating local wound pathology and global metabolic imbalance, which is a promising approach to complex, chronic wounds related to diabetes.